Dolutegravir Solid Dispersions as Oro-Dispersible Tablets: To Ameliorate the Integrase Inhibition Effect - Gottemukkula, Lakshmi Devi; Pathuri, Raghuveer; Sampathi, Sunitha (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Dolutegravir (DTG) is an integrase strand transfer inhibitor that prevents the integration of viral DNA into host cell DNA, which is one of the key phases in the life cycle of HIV, preventing the virus from multiplying inside the host. However, its therapeutic efficacy is constrained by its weak water solubility. Objectives: A simple conventional approach using Sulfobutylether-β-Cyclodextrin (SBE β-CD) and Soluplus® as carriers has been used to ameliorate the effect of DTG. Dispersible tablets have the great advantage of immediately converting a solid into a liquid after administration. Due to that reason, solid dispersions are converted into Oro dispersible tablets by using super disintegrant locust bean gum. Materials and Methods: Three methods were used to prepare solid dispersions: kneading, rota solvent evaporation, and lyophilization. The ratio of DTG to carrier varied between 1:1, 1:2, 1:3, and 1:4 w/w. Optimized DTG solid dispersions were then used in the direct compression method to create Oro-dispersible tablets with the addition of super disintegrants, i.e., locust bean gum and Croscarmellose Sodium. Prepared tablets were evaluated. Results: The drug release for pure DTG is only 14.6%. Lyophilization with SBE β-CD and Soluplus® led to the dissolution of DTG up to 86.17% and 98.11% after 2 hr. The application of Soluplus® significantly improved the solubility and dissolving rate of DTG. The Oro-dispersible tablets made with 12% locust bean gum were the best among the tested formulations. They disintegrated rapidly, taking only 11 sec, and showed the highest dissolution rate of 99.89%, better than the marketed INSTGRATM-50 mg tablets. Optimized rapid disintegration tablets of Dolutegravir can target inegrase and potentially inhibit HIV.
Keywords: Ameliorative effect; Sulfobutylether-β-cyclodextrins; Lyophilization; Locust bean gum; and Soluplus®